A case of mixed-type early gastric cancer with recurrence following curative endoscopic submucosal dissection for expanded indication - Kobayashi, Shunsuke; Nonaka, Satoru; Oda, Ichiro; Abe, Seiichiro; Suzuki, Haruhisa; Yoshinaga, Shigetaka; Taniguchi, Hirokazu; Sekine, Shigeki; Igarashi, Yoshinori; Saito, Yutaka (Endoscopy International Open, 2019)
Background and study aims In Japan, intramucosal gastric adenocarcinoma with ulcerative finding having a predominantly differentiated type with an undifferentiated component, tumor diameter ≤ 3 cm, and no lymphovascular invasion is included in the expanded pathological criteria for curative endoscopic treatment. This indication is based on retrospective examination of surgical resection cases, and is determined to have a negligible risk of lymph node metastasis (LNM). We performed endoscopic submucosal dissection on a 78-year-old man with early gastric cancer in 2011, and pathology revealed a well-differentiated tubular adenocarcinoma (21 × 10 mm in diameter), with poorly differentiated adenocarcinoma components, limited to the mucosa, fibrosis by ulcer scar in the submucosal layer, no lymphovascular invasion, and tumor-free margins. Resection was determined to be curative under expanded indications of the gastric cancer treatment guidelines, 4th edition. However, 55 months after the initial diagnosis, invasive local and distant recurrence was noted. Ultimately, the patient died of gastric cancer 3 months after recurrence.